The use of e-learning in motivating students to excel towards learning outcomes - Hendrik A.E. Lao; Ezra Tari; Ishak Nahas; Hengki Wijaya; I Putu Ayub Darmawan (Intelektual Pustaka Media Utama, 2021)
Researchers focus on the efforts of teachers to improve learning outcomes. Researchers examined the use of e-learning in motivating student achievement on learning outcomes. The influence of student activity on learning outcomes. Student achievement motivation on learning outcomes. The reason for the low quality of student learning makes the author interested in studying this problem. This paper contributes to using e-learning methods, student activeness, and student achievement motivation and can improve learning outcomes. Researchers find a digital-based learning process, the use of e-learning teaching methods in students' achievement motivation towards learning outcomes. The authors see student learning outcomes after using e-learning. Respondents of the study were 35 students who took Christian religious education subjects. The results of the study revealed that independent use of the material received very high scores. Student activeness is carried out correctly and effectively, the highest perceived to be at a mean value of 4.35. Students who take advantage of e-learning have high learning outcomes. The use of e-learning methods, student activeness, and student achievement motivation is implemented correctly and effectively. It was believed to be able to improve the learning outcomes of Christian Religious Education.